272 Optimizing residential automated external defibrillator coverage by targeting social housing areas. (1st May 2022) - Jørgensen, AJ; Kjoelbye, JS; Ettl, F; Krammel, M; Christensen, NB; Ringgren, KB; Torp-Pedersen, C; Folke, F; Hansen, CM
Abstract : Background: Strategies for deployment of automated external defibrillators (AEDs) in residential areas are warranted. Social housing is widespread in Europe, has a high frequency of socio-economic predictors for out-of-hospital cardiac arrest, and consists of well-defined units with local leadership 1 2 . We aimed to optimize AED placement by targeting social housing in Vienna and Copenhagen. Method: Population density was obtained from Urban Atlas 3 ; AED and social housing data from Vienna through City of Vienna, and from Copenhagen through the Danish AED Network and the National Building Foundation, respectively. From April 2020, all 24-hour accessible AEDs in residential areas were included. AED coverage was defined as number of inhabitants within 100 meters of an AED. AEDs were randomly distributed in social housing accounting for current AEDs and a density of 0.5 AED/hectare. Current vs. optimized AED coverage were compared in Vienna and Copenhagen. Results: In Vienna vs. Copenhagen, respectively, 25% (n=492, 752) vs. 31% (n=304, 966) of the population live in social housing areas, characterized by a high average population density: 361 inhabitants/hectare (all residential areas 173) vs. 142 inhabitants/hectare (all residential areas 71). AED density was 0.02 AED/hectare (271 AEDs) vs. 0.12 AED/hectare (1, 641 AEDs) for Vienna vs. Copenhagen, and AED coverage was 358 (95%CI:309;414) inhabitants/AED vs. 119 (95%CI:114;128) inhabitants/AED, respectively. Application of the AED optimization model in social housing increased population coverage by nearly 2-fold: Vienna to 661 (95%CI:628;695, p-value<0.0001) inhabitants/AED; Copenhagen to 243 (95%CI:231;255, p-value<0.0001) inhabitants/AED. Conclusion: AED deployment targeting social housing may be a feasible strategy for optimizing coverage of residential out-of-hospital cardiac arrest. References: Arrigoitia MF, Whitehead C, Scanlon K. Social housing in Europe. First edition. ed. West Sussex, England: John Wiley & Sons; 2014. Folke F, Gislason GH, Lippert FK, Nielsen SL, Weeke P, Hansen ML, et al . Differences between out-of-hospital cardiac arrest in residential and public locations and implications for public-access defibrillation. Circulation 2010;122 (6):623–30. Urban Atlas: The European Commission's Global Monitoring of Environment and Security (GMES) land monitoring service 2018 [Available from: https://land.copernicus.eu/local/urban-atlas/urban-atlas-2018]. Conflict of interest: None declared. Funding: A. J. Jørgensen receives an unrestricted research grant from the private foundation TrygFonden.